Synthetic peptide vaccine for Foot-and- Mouth Disease: synthesis, characterization and immunogenicity - Mansuroglu, Banu; Derman, Serap; Kizilbey, Kadriye; Ates, Sezen Canim; Akdeste, Zeynep Mustafaeva (WALTER DE GRUYTER GMBH, 2020)
Background: The conjugations of antigenic synthetic peptide sequences with carrier polymers have opened new possibilities for the treatment of diseases. In this study, 135-161 peptide sequence of VP1 capsid protein of Foot-and-Mouth Disease was cross-linked with P(VP-co-AA) copolymer by covalent conjugation using water-soluble carbodiimide at different ratio of components (gamma=5, 7, 9, 11, 15) for the first time in the literature. Materials and methods: Bioconjugates were characterized by gel permeation chromatography and fluorescence spectroscopy to identify occurrences of the conjugates. After characterization, gamma=15 bioconjugate was determined as optimum conjugate for immunization studies and IC50 value is calculated as 1.227 mg/mL. By determining the nontoxic range, indirect ELISA were performed to evaluate the immune response elicited in balb/c mice by either peptide or P(VP-co-AA)-peptide bioconjugates (gamma=15). Two injections were applied to each group and high immune responses were obtained against gamma=15 conjugate compared to free peptide and control. Results and conclusion: At the end of 9-week, the general pattern of immunoreactivity was acquired as y=15>>peptide>control. Peptide formulated in the conjugated form had higher antibody response than free peptide and control (p<0.01, for all in both cases), this conjugate formulation put forward the adjuvant activity of P(VP-co-AA) polymer.
Keywords: bioconjugate; Foot-and-Mouth disease; polyelectrolytes; synthetic peptide; toxicity; BOVINE SERUM-ALBUMIN; SOLID PROTECTION; VIRUS; ANTIBODIES; ACID; FMDV; CHROMATOGRAPHY; IMMUNIZATION; COPOLYMERS; MUCOSAL; Biochemistry & Molecular Biology